DEVELOPING STUDENT’S WRITING ABILITY BY OFFERING VARIOUS TECHNIQUES - Siti Azizah (IAIN MADURA, 2013)
Teaching writing is not only giving a topic, asking the students to write, and correcting the students’ tasks but it also means teaching students how to develop ideas and how to make improvements in the drafts in order to produce readable and understandable text for the readers. In other words, students’ writing ability is very much influenced by teacher’s role in class. Therefore, teachers should use purposeful and meaningful teaching strategy to help their students in developing their writing ability. This article describes the role of teacher and the use of various techniques in the process of students’writing.